Variation in the trophic niche and food provisioning between the early and late chick-rearing stages in Magellanic penguins Spheniscus magellanicus at Martillo Island, Tierra del Fuego, Argentina - Dodino, Samanta Graciela; Riccialdelli, Luciana; Polito, Michael J.; Pütz, Klemens; Raya Rey, Andrea Nélida (Marine Biology)
Variation in the foraging niche and parental provisioning behaviors of breeding seabirds have the potential to afect population dynamics (e.g. foraging success, breeding productivity, and ultimately population size). We sampled blood plasma of family’ groups (females, males, and chicks) of Magellanic penguins (Spheniscus magellanicus) from Martillo Island, Argentina. We used stable isotope analyses on plasma samples to examine food provisioning, isotopic niche, trophic position, and diet composition of penguins between the early and late chick-rearing periods. We found clear diferences in the isotopic niches of penguins between the two stages of the chick-rearing period related to shifts in foraging habitat and/or diet composition between stages. We found no evidence of individual consistency in isotopic niches or sex-specifc selective provisioning by adults. In addition, we found high variability within family groups (accounting for 90% of the total isotopic variability). This study improves our understanding of the age, sex, individual, and breeding stage-specifc trophic niches of Magellanic penguins, which may be helpful in projecting how they may respond to future environmental change (e.g., changes that afect prey availability). Fil: Dodino, Samanta Graciela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Polito, Michael J. Louisiana State University Health Sciences Center New Orleans (lsu Health); Fil: Pütz, Klemens. Antarctic Research Trust; Alemania Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina